THE BASIS OF JUDGES ‘CONSIDERATIONS ON DECISIONS OF DIFFERENT RELIGIOUS HERITAGE IN ISLAMIC LAW PERSPECTIVE - Junaidi, Junaidi (Universitas Islam Negeri Raden Fatah Palembang, 2020)
Giving inheritance to heirs of different religions is considered a violation of Islamic law, because it is considered not to maintain Islam. property owned by Muslims should be used as a way to worship, not given to non-Muslims. In the settlement of the case of the Pengadilan Tinggi Agama Palembang, decision Number 05/Pdt.G/2015/PTA.Plg, referring to the Yurisprudensi Mahkamah Agung Number: 51K / AG / 1999, which basically states that heirs who are not Muslim can still get assets from the heir Those who are Muslims based on the